2013
DOI: 10.1159/000347148
|View full text |Cite
|
Sign up to set email alerts
|

Ki-67 Labeling Index Is a Predictor of Postoperative Persistent Disease and Cancer Growth and a Prognostic Indicator in Papillary Thyroid Carcinoma

Abstract: Background: We previously reported that the Ki-67 labeling index (LI) in primary tumors and the thyroglobulin (Tg)-doubling time (DT) were potent prognostic indicators in patients with papillary thyroid carcinoma (PTC). Objectives: To elucidate the relationship between these two factors. Methods: A total of 390 patients with PTC who underwent total thyroidectomy between 1998 and 2004 and in whom the Tg-DT was calculated were enrolled. We determined the Ki-67 LI in primary tumors and compared these values with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 16 publications
1
41
2
Order By: Relevance
“…Tg-DT was recognized as an independent prognostic factor for both DFS and CSS of patients, whereas a short Tg-DT time (less than 1 year) is an indicator of poor prognosis. It was mentioned that Tg-DT is inversely linked to Ki-67 LI and so measurement of Ki-67 may give us information upon post-operative Tg status, Tg-DT, and prognosis of patients [37].…”
Section: Categories Of Thyroid Malignanciesmentioning
confidence: 99%
See 3 more Smart Citations
“…Tg-DT was recognized as an independent prognostic factor for both DFS and CSS of patients, whereas a short Tg-DT time (less than 1 year) is an indicator of poor prognosis. It was mentioned that Tg-DT is inversely linked to Ki-67 LI and so measurement of Ki-67 may give us information upon post-operative Tg status, Tg-DT, and prognosis of patients [37].…”
Section: Categories Of Thyroid Malignanciesmentioning
confidence: 99%
“…Ki-67 labeling index (LI) is generally low in PTC patients; however patients with high Ki-67 labeling index are more likely to show recurrence or persistent disease and to die from carcinoma [24,37]. High Ki-67 LI is considered as an independent prognostic factor for DFS and cause-speciic survival (CSS) [37,38].• BRAF V600E mutation: many previous studies have mentioned that PTC with BRAF mutation is more aggressive, associated with more recurrence, and has poorer prognosis [18,[39][40][41][42]. It has been shown that PTCs with BRAF V600E mutation and negative for X-linked inhibitor of apoptosis protein (XIAP) have higher chance of recurrence [18].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A high Ki-67 LI was found to be a prognostic factor for both the DFS and the CSS of PTC patients, and it was directly related to patient age [39,40]. BRAF V600E mutation is widely recognized as a strong prognostic marker for PTC in foreign countries [41,42], but in Japan, its prognostic value is limited [43,44].…”
Section: Pathological and Molecular Findingsmentioning
confidence: 99%